Rescue of Pink1 Deficiency by Stress-Dependent Activation of Autophagy. Issue 4 (20th April 2017) - Zhang, Yuxi; Nguyen, David T.; Olzomer, Ellen M.; Poon, Gin P.; Cole, Nicholas J.; Puvanendran, Anita; Phillips, Brigitte R.; Hesselson, Daniel
Summary: Stimulating autophagy is a promising therapeutic strategy for slowing the progression of neurodegenerative disease. Neurons are insensitive to current approaches based on mTOR inhibition for activating autophagy, and instead may rely on the Parkinson's disease-associated proteins PINK1 and PARKIN to activate the autophagy-lysosomal pathway in response to mitochondrial damage. We developed a multifactorial zebrafish drug-screening platform combining Pink1 deficiency with an environmental toxin to compromise mitochondrial function and trigger dopaminergic neuron loss. Using a phenotypic screening strategy, we identified a series of piperazine phenothiazines, including trifluoperazine, which rescued Pink1 deficiency by activating autophagy selectively in stressed zebrafish and human cells. We show that trifluoperazine acts downstream of, or parallel to, PINK1/PARKIN to stimulate transcription factor EB nuclear translocation and the expression of autophagy-lysosomal target genes. These data suggest that stress-dependent pharmacological reactivation of autophagy could prevent the loss of vulnerable neurons to slow neurodegeneration. Graphical Abstract: Highlights: New zebrafish screening platform for Parkinson's disease Models mitochondrial dysfunction caused by genetic and environmental risk factors Identified trifluoperazine, which stimulates stress-dependent autophagy Trifluoperazine acts downstream of PINK1/PARKIN to restore TFEB nuclear translocation Abstract : Zhang et al. established an in vivo phenotypic screen identifying autophagy-stimulating compounds that synergized with mitochondrial damage to rescue a zebrafish model of Parkinson's disease.